Perlaksanaan ISO 9000: kajian ke atas firma kontraktor di Malaysia - Othman, Naim (2006)
Quality has received attention in Malaysia’s construction industry as a result of several failures and collapses happened such as highland tower, cracking 31 of 33 middle ring road II (MRR2) piers, school’s computer laboratory problems and the latest is box girder collapse at New Klang Valley Expressway (NKVE). Higher customer expectations, competition and legal action imposed by the local government set new benchmarks for quality concern in the construction industry. It is obvious that more firms are competing for the ISO 9000 certificate as guarantee to strategic competition at international level. This project aims at investigating the benefits to the contractors after the certification of ISO 9000. The study was carried out using literature and analytical methods in which questionnaire and interview techniques were used on contractors as the target respondent. Data were collected and analysed using the statistical package for social science (SPSS) using mean and percentage. The finding indicates that 5 significant benefits exist. These are product quality, staff quality, customer services, firm operation efficiency and competition. The obstacles listed are not greatly deterring the effort of implementing ISO. It is also clear that the respondents are satisfied with ISO implementation. Generally all respondent agree that the significant benefit exist and there is no major obstacle to implement ISO 9000 system and satisfaction over the implementation of ISO 9000 is clearly indicated by respondents.